Manajemen Peningkatan Mutu di Pondok Pesantren - Asichul In’am (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
Management of boarding school Islamic boarding school can be quite good if the implementation of management functions diantarannya planning, organizing, directing, and supervision. With the form before the start of the learning of material planning by ustadz-ustadz and the guidance of akhlaqul karimah in the form, students are disciplined in order to sit, memorize nadhoman, and read the letters of fatihah and prayer before the start of the lesson and the students are told to keep calm in the learning process takes place . The process of improving the quality of educational learning that is applied in a boarding school into a good category can be proved by adannya learning that is taught to students with a division that is tailored to the ability of each. Pesantren management in improving the quality of education in Pondok Pesantren, can be declared quite good if it is proved by the implementation of education management boarding and implementation of management functions diantarannya planning, organizing, directing, and supervision maximally.